Curbing Creative Accounting: Do Religious Environment and Individual Attribute Matter? - Sari, Ratna Candra; Purnama, Ida Ayu; Azizah, Ajeng Wahyu (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 13 No 1 (2018), 2018)
The flexibility of accounting standards is one of the drivers of creative accounting. Creative accounting is an ethical dilemma. It seems that creative accounting does not explicitly violate the rules, but led misinterpretation and misdirection in user’s decision- making. The purposes of this study are, to test the differences of ethical perceptions of creative accounting of undergraduate students in religious and public universities; Second, to examine the effects of moral disengagement on ethical perceptions. The data collection method involved a questionnaire to a total of 225 respondents from two religious-based universities and one public university. Analysis of Variance (ANOVA) was used to test the hypothesis. The results show that there is a significant difference in students’ethical perceptions between public university and religious-based universities. Thus, there is a significant difference in students’ ethical perceptions students with high and low level moral disengagement. Educational implication and suggestion for future research are proposed. Keywords: Ethical perception, creative accounting, ethics education, moral disengagement